Influence of High-Density Community Spaces on the Walking Activity of Older Adults: A Case Study of Macau Peninsula - Xiangyu Chen; Ning Wang; Hua Tang (Buildings)
Macau’s aging communities face growing challenges in meeting the needs of older residents due to rising population density and extremely limited land resources. The concentration of outdated residential buildings—home to a substantial older adult population—exacerbates issues related to age-associated physical decline. For seniors who prefer familiar environments, the spatial constraints inherent in these densely built urban areas increasingly conflict with their specific gerontological needs, indicating the urgent need for urban renewal. This study employs a multi-methodological framework to examine aging populations in Macau’s high-density urban contexts. In Phase I, questionnaire surveys combined with SPSS 26.0-based cluster analysis are employed to (1) stratify older adults according to walking behavior patterns; (2) identify subgroup-specific needs and (3) establish key demographic correlates. Based on the socio-ecological framework, Phase II implements spatial analytics through ArcGIS demarcation of pedestrian catchment areas. This phase further integrates point-of-interest (POI) distribution analysis with space syntax-derived axial map evaluations to formulate typological mobility guidelines for different age cohorts. This study outlines the community walking space requirements of older adults in Macau and explores the influence of high-density community spaces on older adults. A practical evaluation method is proposed to assess age-friendly features of urban pathways, identifying the key environmental factors and their respective impacts. These preliminary findings may inform basic planning principles and adaptive design approaches for older adult-oriented pedestrian spaces.